A systematic review on parent mediated intervention programmes for children with autism spectrum disorders in India - Kalorath, Nigesh; Menon, Sukanya B.; Jayan, C. (International Journal Of Community Medicine And Public Health, 2022)
The relevance of identifying effective interventions and rehabilitation of children with autism spectrum disorders (ASD) increases day by day due to the growth, especially in India. One strategy which has been found to be effective to meet the requirements of children and adolescents with ASD is parent-mediated programmes. However, since most studies of this kind have been undertaken in high-income nations, the present research will explore the effect of parent-mediated intervention programmes in India, a country with a high incidence of developmental disabilities. A fast systematic review employing databases such as PUBMED, psycINFO, Medline, Web of science, and Google Scholar was conducted to assess Indian research on PMI for children with ASD published before February 2022. Studies that were included in the review covered research involving those between the ages of 1 and 18 who were diagnosed with ASD. The 354 research papers were collected, and 11 studies satisfied the criteria for inclusion, including randomised controlled trials and pre-and post-intervention studies. The current research reviewed the articles in terms of the efficacy of parent-mediated interventions (PMI) and their feasibility and acceptability. Studies show that PMI helps improve interactions between parents and children as well as children’s social, communication, motor, and cognitive skills. They also help parents learn more about how to teach their children and improve their children’s language and academic skills. The overall conclusion of the systematic review was that PMI helps improve parent and child skills.